2020
DOI: 10.34172/apb.2021.009
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Mechanical Properties of Denture Base Material as a Vehicle for Novel Hydroxyapatite Nanoparticles Loaded with Drug

Abstract: Purpose: This study aimed to evaluate the biological and mechanical properties of the poly(methyl methacrylate) (PMMA) denture base material as a vehicle incorporating novel hydroxyapatite nanoparticles (HA-NP) loaded with metronidazole (MZ) drug. Methods: HA-NP was prepared via wet-chemical-method, characterized by XRD, SEM/EDX, TEM, Fourier-transform infrared spectroscopy (FTIR), as well as the measurement of surface area and pore-size distribution. Four drug delivery formulas were prepared in the form of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 45 publications
(58 reference statements)
1
21
1
Order By: Relevance
“…Comparing the hardness values obtained for the HP and AP specimens, the lower values for the AP specimens were due to the presence of residual monomers, which act as a plasticizer and induce poor mechanical properties and low scratch resistance ( Gad et al, 2017b , Xu and Burgess, 2003 ). Elboraey et al, (2020) found a decrease in hardness with the addition of hydroxyapatite nanoparticles (HA-NP), which does not agree with the finding of the present study. The different results may be due to differences in filler type, size, and concentrations used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Comparing the hardness values obtained for the HP and AP specimens, the lower values for the AP specimens were due to the presence of residual monomers, which act as a plasticizer and induce poor mechanical properties and low scratch resistance ( Gad et al, 2017b , Xu and Burgess, 2003 ). Elboraey et al, (2020) found a decrease in hardness with the addition of hydroxyapatite nanoparticles (HA-NP), which does not agree with the finding of the present study. The different results may be due to differences in filler type, size, and concentrations used in these studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Specimens were applied on the selected microorganisms ( Bacillus subtilis (+) (ATCC 6633), Staphylococcus aureus (+) (ATCC 6538), Escherichia coli (−) (ATCC 2592), Pseudomonas aeruginosa (−) (ATCC 27853) and Candida albicans (Yeast) (ATCC 10231) utilizing shake cup technique to ascertain the antimicrobial properties through (%) decrease of these microorganisms inclusion with the microorganisms contrasted with the quantity of the microorganism's cells before the inclusion (control) for 24 hr period 14 . The level of pathogenic microorganism decrease after contact with the selected microorganisms was estimated utilizing spectrophotometer (Perkin‐Elmer Lambda EZ 201 UV–Vis‐USA) and contrasted to control bacterial strain.…”
Section: Methodsmentioning
confidence: 99%
“…decrease of these microorganisms inclusion with the microorganisms contrasted with the quantity of the microorganism's cells before the inclusion (control) for 24 hr period. 14 The level of pathogenic microorganism decrease after contact with the selected microorganisms was estimated utilizing spectrophotometer (Perkin-Elmer Lambda EZ 201 UV-Vis-USA) and contrasted to control bacterial strain.…”
Section: Biomineralizationmentioning
confidence: 99%
“…Based on the idea that hydroxyapatite is a biocompatible and biodegradable naturally existent material in bones and teeth, Elboraey et al 22 aimed to develop biodegradable HA-NP that are capable of acting as carriers for metronidazole (MZ) within denture base resin in an attempt to manage oral infections. The results were promising in which there was a sustained release of MZ for up to 1 month.…”
Section: Hydroxyapatite Nanoparticlesmentioning
confidence: 99%
“…The excessive unreacted monomer acts as a plasticizer that allows the deformation of the material under load. 22…”
Section: Physical Properties Of Rechargeable Denture Base (Mechanical...mentioning
confidence: 99%